2013
DOI: 10.1186/1752-1505-7-15
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and mental health of medics in eastern Myanmar’s conflict zones: a cross-sectional and mixed methods investigation

Abstract: BackgroundIn conflict and disaster settings, medical personnel are exposed to psychological stressors that threaten their wellbeing and increase their risk of developing burnout, depression, anxiety, and PTSD. As lay medics frequently function as the primary health providers in these situations, their mental health is crucial to the delivery of services to afflicted populations. This study examines a population of community health workers in Karen State, eastern Myanmar to explore the manifestations of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…Participants in the current study reported higher levels of trauma than those found in other "traumatized" populations of health providers working in conflict zones in Eastern Myanmar (M ϭ 10.7, SD ϭ 5.0; Lim, Stock, Shwe Oo, & Jutte, 2013) or among long-term refugees in Nepal (M ϭ 13.77, SD ϭ 7.01; Jordans, Semrau, Thornicroft, & van Ommeren, 2012). Furthermore, when cases were identified using the presence/absence scoring method, one fifth (19.9%) of the sample reported values above the cutoff for the GHQ-12.…”
Section: Resultsmentioning
confidence: 76%
“…Participants in the current study reported higher levels of trauma than those found in other "traumatized" populations of health providers working in conflict zones in Eastern Myanmar (M ϭ 10.7, SD ϭ 5.0; Lim, Stock, Shwe Oo, & Jutte, 2013) or among long-term refugees in Nepal (M ϭ 13.77, SD ϭ 7.01; Jordans, Semrau, Thornicroft, & van Ommeren, 2012). Furthermore, when cases were identified using the presence/absence scoring method, one fifth (19.9%) of the sample reported values above the cutoff for the GHQ-12.…”
Section: Resultsmentioning
confidence: 76%
“…Cluster 1 was the most varied cluster, indicated by extreme branching within the cluster dendrogram. CCDs included Kareni seik lo’shaa (Lim, Stock, Oo, & Jutte, 2013), Latino susto (Baer et al, 2003), and Yemeni fijac (Swagman, 1989). Because of the prominence of somatic symptoms and nonspecific dysphoric symptoms, we labeled Cluster 1 somatic dysphoria.…”
Section: Resultsmentioning
confidence: 99%
“…In other programs, peer support is likely happening within the context of peer supervision, though their support of one another has not been closely studied. An example of a method to mobilize this organic peer support process was adopted in a study in Myanmar through providing workshops for trauma management medics to learn techniques to promote personal and peer mental wellbeing [51]. By providing lay providers with both the tools and collaborative spaces to work through their issues, such as with peer support groups or targeted workshops, they can become more proactive in dealing with problems that may arise in their work.…”
Section: Implications/recommendationsmentioning
confidence: 99%